Video Steganography using MATLAB - G. Paramesh; K. V. Pavithra; N. Ranjitha; S. Swetha; T. Anushalalitha (EAI Endorsed Transactions on Cloud Systems, 2017)
This paper discusses a Video Steganographic scheme that can provide approvable security with high computing speed, by embedding data in video frames. The technique of embedding data in a video file by using LSB before which the secret information is encrypted using symmetric XOR operation, thereby providing two layers of security. Data Hiding andExtraction procedure are experimented successfully. All experiments are done using Matlab 2010a simulation software. This method proves to be more efficient than other methods with the amount of data that can be embedded in it, showing a PSNR of above 30 dB.